ByzRev 02.2020.024: Melpomeni Vogiatzi, Byzantine Commentaries on Aristotle’s Rhetoric. Anonymous and Stephanus, In Artem Rhetoricam Commentaria: (Commentaria in Aristotelem Graeca et Byzantina 8). Berlin – Boston: De Gruyter 2019. - Maksimczuk, José (The Byzantine Review, 2020)
Melpomeni Vogiatzi, Byzantine Commentaries on Aristotle’s Rhetoric. Anonymous and Stephanus, In Artem Rhetoricam Commentaria (Commentaria in Aristotelem Graeca et Byzantina 8). Berlin – Boston: De Gruyter 2019. 268 pp. – ISBN: 978-3-11-062675-9 (€ 109.95)